Close the gap: contextual influences on defensive dispersion in rugby league - Collins, N.; Sawczuk, T.; Whitehead, S.; Jones, B. (International Journal of Performance Analysis in Sport, 2026)
On-field spacing has been linked to successful performance in a number of sportsto date, there is limited research investigating this within rugby league. This study aims to (a) quantify the defensive dispersal during rugby league match-play and (b) identify if contextual factors are associated with the dispersal. Global Positioning System data were analysed from 47 European Super League matches (1598 player files). Defensive dispersal was calculated for 1959 defensive sets of rugby league. Linear mixed models were used to analyse the effects of contextual factors on the average defensive dispersal per set when accounting for team and fixture. On-field position and match half were found to significantly affect defensive dispersal. However, set length, play-the-ball length, and final score difference were found to have minimal impact on defensive dispersal. This study demonstrates that defensive dispersal in rugby league can be measured using GPS data and may be strongly influenced by on-field positioning. As such, it quantifies an important element of tactical preparation for rugby league teams.